Peran Islam dalam Pembangunan Masyarakat Kota Ambon, Provinsi Maluku (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
The citiy of Ambon, as the capital of Maluku Province, has diverse cultures and religions, including Islam. However, despite the majority of the population being Muslim, there has been limited research on the roles of Islam in Ambon. This study aims to analyze the role of Islam in community development in Ambon, Maluku Province, using a qualitative approach with a case study method. Data was obtained from in-depth analysis of the field and interviews with Islamic community leaders, government officials, and Islamic institutions' administrators in Ambon. In addition, data was collected from relevant documents and archives for the study. The results showed that Islam plays a significant role in community development in Ambon, especially in education and economic empowerment. Islamic educational institutions such as madrasah and pesantren have contributed to improving human resources quality in Ambon. Furthermore, Islam also contributes to infrastructure development and public facilities. Islamic institutions such as social and charitable foundations are active in providing social and humanitarian services to the people of Ambon, especially in emergency situations and natural disasters. However, there are still obstacles in implementing the role of Islam in community development in Ambon. One of them is the lack of coordination and synergy between the government and Islamic institutions in implementing development programs. Additionally, there are still differences in views and understandings among those involved in community development in Ambon. Therefore, efforts are needed to improve coordination and synergy between the government and Islamic institutions in development programs in Ambon.